Implementasi Metode SMARTER (Simple Multi Attribute Rating Technique Exploiting Rank) Penentuan Calon Pendonor Darah - Muhammad Ali; Dian Megah Sari; Muh. Rafly Rasyid (PPPM Institut Teknologi Pagar Alam, 2026)
Limited blood supply and increasing demand for transfusions require an accurate and objective selection process for potential blood donors. Determining donor eligibility is still done manually, which can potentially lead to inaccurate decisions. This study was conducted with the aim of applying the SMARTER method in developing a decision support system for determining the eligibility of potential blood donors at the Indonesian Red Cross (PMI) in Majene. The SMARTER method was used because it can accommodate various criteria with Rank Order Centroid (ROC) weighting based on their level of importance. The criteria used include blood pressure, hemoglobin level, body weight, medication consumption, age, length of last sleep, and medical history. Data was obtained through observation, interviews with PMI officers, and literature review. The calculation results show that the SMARTER method is capable of producing an objective ranking of alternatives. Of the five prospective donors tested, alternatives A1 and A3 obtained the highest preference value of 0.6314 and were declared eligible as blood donors. Thus, the SMARTER-based decision support system can help improve the effectiveness and accuracy of the blood donor selection process.